A 10-Year Retrospective Analysis of Methyl Aminolevulinate Photodynamic Therapy Consultation at the Hospital de Braga. Issue 2 (June 2016) - Brito, Celeste; Resende, Cristina; Oliveira, Pedro
Abstract Introduction Photodynamic therapy (PDT) is a well-established treatment for actinic keratosis (AK), basal cell carcinoma (BCC), and Bowen's disease (BD). The object of this study was to describe the results of a retrospective analysis of patients treated with methyl aminolevulinate PDT (MAL-PDT) with red light, over the past decade at the Hospital de Braga (Braga, Portugal). Methods This study is based on the retrospective analysis of the clinical records of patients treated with MAL-PDT from January 2003 to December 2013. Results More than 550 patients with mean age of 72 years were treated with MAL-PDT. About two-thirds of these patients were female. In terms of diagnostics, 67% of the patient population were affected with AK, 27% presented with BCC, and 4% had BD. With an average follow-up of 5.5 years, 99.5% of the lesions had cleared. The recurrence of lesions occurred during the first year of follow-up, mostly large BCC localized on the trunk. Conclusion This study showed the excellence of MAL-PDT for treating AK, BCC, and BD, with a low recurrence rate.